A numerical investigation into stripping failure of bolt assemblies at elevated temperatures. (October 2020) - Shaheen, Mohamed A.; Foster, Andrew S.J.; Cunningham, Lee S.; Afshan, Sheida
Abstract: A detailed finite element (FE) study is presented investigating the factors affecting the failure modes of high strength and stainless steel bolt assemblies under tensile force at ambient and elevated temperatures. Axisymmetric FE models incorporating key behavioural aspects including surface interaction and damage modelling of steel at elevated temperatures were developed. In practice, stripping failure is generally undesired because it results in premature failure of the bolt which can deteriorate rotational capacity of connections and hence compromise the robustness of steel frames. Yet, stripping failure has not been previously investigated in the open literature. In this study, the examined stainless steel bolt assemblies displayed an outstanding ductile response even when stripping failure was observed. Parameters that can govern the failure modes of bolt assemblies at elevated temperatures include the thread length in the grip ( L t ), and the relative strength and friction between the mating threads. At ambient temperature, stripping was observed at certain L t lengths depending on the nut dimension deviation from the basic profile. The L t stripping failure threshold reduces with temperature for high strength bolt assemblies while the value fluctuates without a discernible pattern for stainless steel types. Increasing the relative strength and friction coefficient can reduce the L t length threshold, with the former having the greatest influence. It was also found that larger bolt sizes are more vulnerable to thread stripping failure.